Exploring Perceived Social Support from Peer Facilitators in an HIV Treatment Adherence Intervention for African American Patients: A Content Analysis of Participant Perspectives. (2nd February 2015) - Houston, Eric; Osborn, Amanda; Lyons, Thomas; Masvawure, Tsitsi; Raja, Sheela
ABSTRACT HIV treatment adherence interventions increasingly rely on peer facilitators to promote treatment adherence and improve patient retention, yet little is known about how participants perceive the role performed by peer facilitators. The present study examined participant perceptions in terms of the social support from peer facilitators in a hospital‐based intervention in Chicago. Content analysis was conducted with reference to four types of social support (instrumental, informational, emotional and affiliational) on exit interviews with 11 participants enrolled in the intervention that targeted African‐American patients living with HIV/AIDS. We examined how the type of social support perceived by participants was related to their self‐reported behaviours in three domains: adherence, sexual safety and general coping. Our analysis revealed that most participants perceived informational and emotional support from their peer facilitators, followed by instrumental support. Affiliational support was the least frequently perceived type of social support. We found that perceived informational support from peer facilitators with regard to adherence had greater impact and credibility amongst participants than the same type of support from medical providers. Informational support was cited most frequently with regard to influencing adherence and sexual safety behaviours, whereas perceived emotional support was cited primarily with helping participants cope with HIV. Copyright © 2015 John Wiley & Sons, Ltd.